PATHOLOGICAL AND MOLECULAR DIAGNOSIS OF PARATUBERCULOSIS AMONG DROMEDARY CAMELS IN SAUDI ARABIA - A. M. Hereba; M. A. Hamouda; F. A. Al-Hizab (Journal of Animal and Plant Sciences, 2015)
This study was conducted on dromedary camels suffering from disease suspected Johne’s disease. The clinical signs were chronic watery diarrhea, emaciation and decreased milk production. Inter-mandibular edema was noticed in two cases. Several investigations were performed, staining of intestinal smears with Ziehl–Neelsen stain, histopathology and PCR. Gross pathological examination revealed thickening of the intestinal wall with corrugation of the mucosa which extend in some cases to the colon and rectum along with granulomatous reaction in the liver. Mesenteric and ileocecal lymph nodes were moderately large and edematous. Histopathological lesions were diffuse granulomas characterized by extensive macrophages and epithelial cell infiltration into the mucosa and submucosa of the small intestine, and colon, with numerous acid-fast organisms. The ileocecal lymph node as well as the other mesenteric lymph nodes showed sinus histicytosis, infiltration of macrophages and epithelial cells containing acid-fast bacilli. The different tissue, organs and fecal sample of infected camels with Mycobacterium avium subspecies paratuberculosis were strongly positive by IS900 PCR. In conclusion, the present study suggests more than one tool for the diagnosis of Johne’s disease in dromedary camel.
Keywords: Dromedary camel; paratuberculosis; PCR; histopathology